A night of magic the Lantern Festival in Taiwan - Chung, Hsiu-hsien; Wong, Albert; Kwang Hwa Mass Communication ([Taiwan] : Kwang Hwaa Mass Communications, 2007)
The Lantern Festival marks not only a change of season, but also an important passing point in people's hearts. Tens of thousands of lanterns and firecrackers are lit all across Taiwan, sending the island population's prayers for blessings, good fortune, and wealth to the many gods that look over them
Executive producer, Nan-hung Lin ; supervisor, Wen-tsang Chung ; supervisor producer, William J.T. Yih
DVD Format
Audio available in Chinese, English, French and Spanish for disc 1 and German, Japanese and Russia for Disc 2
Keywords: Festivals -- Taiwan; Festivals -- China